Heterotrophic bacterial production and extracellular enzymatic activity in sinking particulate matter in the western North Pacific Ocean - Yamada, Namiha; Fukuda, Hideki; Ogawa, Hiroshi; Saito, Hiroaki; Suzumura, Masahiro (Frontiers in Microbiology, 2012)
Heterotrophic activities on sinking particulate matter (SPM) play an important role in SPM fluxes in the ocean. To demonstrate regional differences in heterotrophic activities on SPM, we measured heterotrophic bacterial production (HBP) in seawater (HBPSW) and SPM (HBPSPM) as well as potential extracellular enzyme activity (EEA) in SPM on a transect along 155°E in the western North Pacific Ocean in the subarctic (44°N), the Kuroshio Extension area (35°N), and the subtropical gyre (20°N). Depth-integrated HBPSW from the surface to 500 m was comparable between the locations, whereas HBPSPM at 44°N was substantially lower than at the other sites. We found the highest particulate organic carbon (POC) export flux and export efficiency to bathypelagic depths, and the lowest water temperatures, at 44°N. We found significant correlations between leucine aminopeptidase (LAPase) activity, β-glucosidase (BGase) activity, POC flux and particulate organic nitrogen flux. LAPase activity was two orders of magnitude higher than BGase activity, with a BGase:LAPase activity ratio of 0.027. There were no significant correlations between HBP and EEA in SPM except for lipase, and lipase activity was significantly correlated with temperature. We propose that hydrographic conditions are an important factor controlling heterotrophic bacterial activity and export efficiency of organic carbon to the deep ocean, as are the sources and abundance of SPM produced in the euphotic zone via primary production.